(untitled) (E Global Congress, 2024)
One of the important measures taken in the organization of modern education is to achieve high results in a short time, without excessive mental and physical exertion. Among short periods of time, the supply of certain theoretical knowledge to students, the formation of skills and competencies in them on a certain activity, the control of the activities of students, the formation of skills and competencies on the knowledge, skills acquired by them, as well as the control of the activities of students, the assessment of the level of knowledge, skills and Today, in a number of developed countries, kata experience has been accumulated in this regard, and the methods that make up the foundations of this experiment are carried out in the name of interactive methods.